Development and initial configuration of the city of San Miguel through the institution of the encomienda (1532-1578) - Elías Lequernaqué, Jorge Pável (2011)
This preliminary study focuses on how the "encomienda turned out to be a vital element in the initial configuration of the San Miguel city, as well as in its subsequent development and ist consolidation about 1578, when the city was moved to a second place in the port of Paita. This study notices that the indigenous demographic reduction affected the amount of the tax, which changed the actions of the encomenderos in the political, social and economic life of the city.